ISLAMIC CONTRIBUTIONS IN THE FIELDS OF ART AND SCIENCE - Elok Faiqoh; Najmawati Sulaiman (Jurnal Ilmiah Publipreneur, 2020)
The discussion of islamic contributions in the fields of art and science is very much embedded in the history of islamic civilization and culture. The rapid growth of Islam is recognized as a most influential civilization. Through this study, researchers invited readers to learn more about the contribution of Islam to the development of world civilization in both the fields of art and science. Descriptive research is used in this study because the information used in this study is wordplay rather than numerical figures obtained from the yellow scriptures, journals, magazines, newspapers, and books. The form of islamic contribution in arts by al-Ghozali talks about the art law itself being poured in his magnum opus (his masterpiece) of Ihya' 'Ulumuddin'. Whereas in science there are al-Khawarizmi with its discovery in the books of al-Jam’a wal Tafriq bil Hisab al-Hindi, al-falaki with astrological predictions in the books of al- 'uluf, ibn haytam and al-khoziny with optical and gravitational theories in the books of al-manadzir and mizanul hikmah, ar-razi the discoverer of fontanel's thread, in modern sociology ibn khaldun with the work of the Muqaddimah, and Avicenna in medicine of the Qanun fi at-Tib.